Anti-Markovnikov hydroallylation reaction of alkenes via scandium-catalyzed allylic C‒H activation - Shiyu Wang; Lichao Ning; Tao Mao; Yuqiao Zhou; Maoping Pu; Xiaoming Feng; Shunxi Dong (Nature Communications)
Abstract Compared with rare-earth (RE)…heteroatom interaction, RE…π interaction, frequently used in facilitating regio- and stereoselectivity of olefin polymerizations, is seldomly used to trigger catalytic C − H functionalization. Here, we describe a direct anti-Markovnikov hydroallylation reaction of styrene derivatives with 1-aryl-2-alkyl alkenes and α-alkenes by use of RE…π interaction. This protocol provides a straightforward and atom-efficient route for the synthesis of valuable chain elongated internal alkenes (65 examples, up to 99% yield, > 19:1 E/Z ratio). The reaction proceeds via an allylic Csp3‒H activation pathway initiated by site-selective deprotonation with the assistance of cationic imidazolin-2-iminato scandium alkyl species followed by alkene insertion into the resulting scandium-allyl bond. A catalytic amount of Lewis base additives, such as amine and tetrahydrofuran (THF) show significant effects on the reactivity and E/Z selectivity. The reaction mechanism is elucidated by experimental studies and theoretical calculations.